GEOECOLOGICAL ORIENTATION OF LOGISTICS MANAGEMENT OF PRODUCTION AND SERVICE SYSTEMS - Смирнов, Ігор (Human Geography Journal, 2015)
Revealed the logistics impact on environment, environmental security issues, circular strategy for efficient processing, reverse logistics and its objectives, logistics system of waste management. Showed the nature and methods of geoecological orientation of logistics management of production and service systems. On specific examples, the algorithm of cost calculation, which is achieved by the introduction of environmental management approaches to logistics systems in manufacturing and service is disclosed. Given major logistics solutions to such problems of production and service systems, as selection modes; study the structure of logistic units and their forms; companies cooperation of logistics projects; rational configuration of logistics units.